ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP MUTIARA 1 BANDUNG PADA MATERI BENTUK ALJABAR - Siti Romlah; Gida Kadarisma; Wahyu Setiawan (Journal on Education, 2019)
The purpose of this study was to describe the mathematical communication skills of students of SMP 1 Bandung Junior High School class VII and examine errors in solving test questions regarding the material in the form of algebra. The research method used is the description method. The subject of the research was conducted on 29 students of Grade 1 Pearl Junior 1 Bandung Bandung. The test questions given are in the form of 6 questions. The results showed that mathematical communication skills as a whole were moderate and there were 1 indicator that entered the criteria very well, namely for indicators to rewrite information in the form of images into the language of mathematics. (Well); indicators state the problem of mathematical models of story forms into mathematical symbols, (Good); the indicator states what is known and asked according to the mathematical formula (Good), the indicator completes what is known and what is asked daily events using mathematical formulas (Good). And 1 indicator which includes sufficient criteria, namely the indicator states the completion of the mathematical model of drawing with the right solution idea. And it can be seen that the average score of all questions from all students is included in the good criteria